Effectiveness of Footwork and Handwork Drills in Enhancing the Female College Student’s Dribbling Skills (British Journal of Multidisciplinary and Advanced Studies, 2023)
Basketball is a widely loved sport around the globe. However, it can be a challenging sport to learn, especially for inexperienced players like female non-athlete college students. This study investigated the effectiveness of footwork and handwork drills in enhancing the dribbling skills of female college students (N=68) from a private tertiary school in Cagayan de Oro City, Philippines. A quasi-experimental design was employed to determine the effectiveness of the two interventions. The footwork and handwork drills were found to be effective in improving the participants' dribbling skills when performed regularly, such as three times a week for four consecutive weeks. The groups significantly differed in their scores (t=2.21, p=.031), with the footwork drills group having a higher mean than the handwork drills group. This implies that the footwork drills intervention was more effective than the handwork drills intervention in improving the students' dribbling coordination skills. These findings confirm the assumption that footwork and handwork drills could enhance the dribbling skills of female college students. The interaction between the system dynamics theory and motor learning theory helped explain the improvement in the students' dribbling skills. The findings point to student-athletes needing footwork drills to enhance their dribbling skills and lessen the possibility of injuries when participating in physical activities.